PENERAPAN GIZI SEIMBANG SELAMA MASA PUASA DI DESA PERBARAKAN, KECAMATAN LUBUK PAKAM TAHUN 2021 - Delita Br Panjaitan; Raisha Octavariny; Sri Melda Bangun; Anggi Isnani Paranduri; Ade Julfiani Ritonga (JURNAL PENGMAS KESTRA (JPK), 2021)
As an obligation carried out by Muslims, fasting is a partial fasting group, namely fasting that is carried out periodically. One indication of fasting is categorized as good if it begins with breaking the fast, ending sahur, stopping eating before being full. During the fasting period, it is highly recommended to maintain a balanced diet. In addition to the nutritional content, the form / type of food served also needs to be considered so that the implementation of fasting goes well and without causing health problems, especially in the stomach organ. This PKM activity was carried out with the aim of increasing knowledge and understanding in the application of balanced nutrition during fasting worship with the target of PKK mothers in Perbarakan Village, Lubuk Pakam District. Pre and post tests were conducted to see if there was an increase in understanding of balanced nutrition. Activities are carried out by providing information in the form of balanced nutrition counseling and tips on how to manage balanced nutrition in the family. The implementation time of the activity is 1 week with a total of four meetings. After the counseling is done, it is hoped that there will be an increase in knowledge about balanced nutrition which will later be applied in their respective homes during the fasting period. During the extension, the implementation team also provided props in the form of food models and leaflets. The results obtained can be observed in the graphic images that will be displayed where there is an increased understanding of balanced nutrition. In addition, the existence of teaching aids also helps facilitate the delivery of balanced nutrition material.